Reporting practices of Malaysian public universities: The extent of accountability disclosure - Ismail, Suhaiza; Abu Bakar, Nur Barizah (Academic Journals, 2011)
The study intends to evaluate the extent to which Malaysian public universities disclose accountability information in their annual report and on their website. It also compares the degree of annual report and website disclosure between established and new universities in Malaysia. Content analysis was undertaken using the disclosure index that was developed based on the items listed in the Malaysian Government Treasury Circular (MGTC) 4/2007 and selected items from the Modified Accountability Disclosure (MAD) index. Mean disclosure index was computed to examine the disclosure levels.There is evidence that Malaysian public universities have to some extent disclosed relevant information in their annual report but the level of information published on the website is considered very low. Additionally, established universities’ group is better off in terms of information disclosure for both channels of communication. The number of universities that participated in the analysis is relatively small, and the study mainly considers the extent of disclosure but not the quality of the information disclosed. Greater enforcement from the government is required to ensure greater disclosure of information in the universities’ annual report and on the website. This study offers some insights into the current reporting practices of Malaysian public universities using two reporting mediums, the annual report and website.